Ghostly echoes - Ritter, William, 1984- (Ritter, William, 1984- Jackaby series., 2016)
"The highly anticipated third volume of the paranormal detective series perfect for "readers who enjoy Doctor Who, Supernatural, Grimm...and of course, Sherlock Holmes stories, and who are ready to say up into the wee hours." Jenny Cavanaugh, the ghostly landlord of 926 Augur Lane, has enlisted the services of her detective-agency tenants to solve a decade-old murder--her own. Abigail Rook and her eccentric employer, R. F. Jackaby, dive into the cold case, starting with a search for Jenny's fiancé, who went missing the night she died. But when a new, gruesome murder closely mirrors the events of ten years prior, Abigail and Jackaby realize that Jenny's case isn't so cold after all, and her killer may be far more dangerous than they suspected. Fantasy and folklore mix with mad science as Abigail's race to unravel the mystery leads her across the cold cobblestones of nineteenth-century New England, down to the mythical underworld, and deep into her colleagues' grim histories to battle the most deadly foe she has ever faced" --